Efficacy of newly Synthesized Pesticidal Chemical ‘4-[3-(4-Biphenyl)-1,6-Dihydro-6-Iminopyridazin-1-yl] Butyronitrile hydro Bromideon bean Aphid, Aphis craccivora Koch (Homoptera: aphididae) (Bangladesh Journal of Zoology, 2022)
A study was carried out to determine the effectiveness of newly synthesized chemical ‘4-[3-(4-biphenylyl)-1, 6-dihydro-6-iminopyridazin-1-yl] butyronitrile hydro bromide against beanaphid, Aphis craccivora, under six treatments: T1 (20 ppm), T2 (40 ppm), T3 (60 ppm), T4 (80 ppm), T5 (100 ppm), and untreated control T6. Aphid numbers was peaked in January and it was zero in February. The best efficacy of administered doses was found in the T3 and followed by T5, T4, and T2, respectively. The aphid abundance in different weeks (F= 1.89; p